Efficient production system for hydrogel-based transparent soil for plant root observation - Naoyuki Sotta; Wenhao Li; Toru Fujiwara (BioTechniques)
Observation of plant root morphology in soil is of fundamental importance in plant research, but the lack of transparency of the soil hampers direct observation of roots. One of the approaches to overcome this technical limitation is the use of “transparent soil” (TS), hydrogel-based beads produced by spherification of gelling agents. However, the production of TS by natural dripping of gelling solution can be labor intensive, time consuming and difficult to maintain consistent product quality. Here we present a semi-automated system for TS production. A three-channel peristatic pump controls the critical parameters for spherification, such as drop height and ionic strength, allowing larger-scale TS production with less manual operation. This system improves the efficiency of experiments using TS and enables large-scale experiments requiring large amounts of TS.